A Study on the Application of Solar Panel Technology in Low-Income Residential Housing in Deli Serdang Regency - Dicky Andrea Sembiring; Ahmad Mansuri; Ferry Rahmat Astianta Bukit; Malinda Sari Sembiring (International Journal of Architecture and Urbanism, 2021)
The need for energy use, especially electrical energy continues to increase from year to year. One of the sectors that consume the largest electrical energy is the household sector which consumes about 27% of the total energy consumption of all sectors. The main energy source in Indonesia at this time still comes from fossil energy, although the government has tried to develop various renewable energy sources for the future. Solar energy is one of the renewable energies that is quite potential for Indonesia considering the level of solar radiation in Indonesia is quite high throughout the year. The selection of subsidized housing as the object of research is due to the existence of clear regulations and the number which also continues to increase every year. Through the collection of physical data on the research location, such as analysis of shadows, roof structure, solar irradiation data, average electric power usage, the average solar energy requirement of the subsidized housing will be obtained. Furthermore, by calculating the economic value, it will be obtained how the description of the possibility of applying solar energy to subsidized housing will be obtained. If possible, the application of solar energy in subsidized housing can help government programs to use renewable energy and reduce the use of fossil energy